The Primary Reading/Writing Education Process in Light of the Views of Mothers, Who Learn Reading/Writing in Turkish, and Their Children - Mustafa Yeniasır; Burak Gökbulut (Qubahan Academic Journal)
The primary reading and writing education process is one of the most crucial experiences that shape individuals’ future lives and influence their achievements throughout life. With the help of acquired reading and writing skills, individuals learn their societal values and ensure that the society, in which they live, will look toward the future more confidently. Today when information is intensively produced and consumed, whether a person’s existence is acknowledged and whether a person continues to succeed are directly connected to whether a good quality reading and writing education was received by the person in the past. The goal of this research is to evaluate and analyze the views of mothers, who participated in the primary education course on reading and writing in Turkish at the Turkish Cypriot Child Protection Institution in the Turkish Republic of Northern Cyprus approximately for five months in the spring semester of the 2022-2023 academic year, as well as the views of their children, who closely followed up the process. With this goal, a study was carried out with 15 mothers, who participated in the above course, and 15 children, who stood by their mothers during this process. Mothers and children participating in the study were asked to narrate the memories of their experiences during the primary education course on reading and writing in Turkish. The research data were collected via face-to-face interviews and written documents. The thematic analysis method was used in the analysis of research data, and themes produced from written documents were categorized into sub-themes and were evaluated.